Frequency, management and impact of adverse events on treatment outcomes in patients with multidrug resistant tuberculosis in Balochistan, Pakistan - Sara Rafique; Nafees Ahmad; Shereen Khan; Amjad Khan; Muhammad Atif; Abdul Wahid; Asad Khan; Hira Waheed (Taylor & Francis Group, 2024)
ABSTRACTBackground: Early detection, monitoring, and managing adverse events (AEs) are crucial in optimising treatment for multidrug-resistant tuberculosis (MDR-TB) patients.Objectives: To investigate the incidence, factors, management, and impact of AEs on treatment outcomes in MDR-TB patients.Methods: This study reviewed the medical records of 275 MDR-TB patients at Fatimah Jinnah Institute of Chest Diseases in Quetta, Pakistan. Patient information was collected using a designed data collection form. Mann-Whitney U and Kruskal-Wallis tests examined the difference in AEs occurrences based on patients' characteristics. Multiple binary logistic regression identified factors associated with unsuccessful outcomes, with statistical significance set at a p-value < 0.05.Results: Almost all patients (99.6%) experienced at-least one AE (median = 4/patient, interquartile range:3-6). The most common were GI disturbance (95.3%), arthralgia (80.4%), body pain and headache (61.8%), ototoxicity (61.4%), psychiatric disturbance (44%), hypokalaemia (40.4%), dermatological reactions (26.2%) and hypothyroidism (21.5%). AEs led to treatment modification in 7.3% patients. Educated patients, those with a history of TB treatment, previous use and resistance to any second-line drug had significantly higher number of AEs. A total of 64.0% were declared cured, 3.6% completed treatment, 19.6% died and 12.7.9% were lost to follow-up. Patients' age of 41-60(OR = 9.225) and >60 years(OR = 23.481), baseline body weight of 31-60 kg(OR = 0.180), urban residence(OR = 0.296), and experiencing ototoxicity (OR = 0.258) and hypothyroidism (OR = 0.136) were significantly associated with unsuccessful treatment outcomes.Conclusion: AEs were highly prevalent but did not negatively impact treatment outcomes. Patients at higher risk of developing AEs and unsuccessful outcomes should receive special attention for its early management.